The ultrastructure of mouse articular cartilage: Collagen orientation and implications for tissue functionality. A polarised light and scanning electron microscope study and review - Hughes L. C.; Archer C. W.; ap Gwynn I. (European Cells & Materials, 2005)
Adult mouse articular cartilage (AC) has not been thoroughly described using high resolution imaging techniques, despite the fact that the availability of knockout mice with specific extracellular matrix (ECM) mutations have renewed interest in using the mouse as a model for a variety of different human conditions. With osteoarthritis affecting millions of people worldwide, investigations into the structure and, therefore, the ability of AC to act as a load-bearing tissue, are crucial for developing treatments and prevention techniques to limit the degree of severity in this condition. Cryofixation and formaldehyde fixation as well as chemical digestion of the uncalcified regions of AC were used in combination with bright field light, polarised light and scanning electron microscopy to image the structure of adult mouse AC. Chemical digestion of the tissue revealed unique insights into the structure of mouse AC and the high cellular density of the tissue. Tightly packed sheets of collagen fibrils formed the territorial matrix (TM) of the deep zone. These were observed closely surrounding the chondrons, after applying both chemical and cryofixation techniques. The interterritorial matrix (IM), in contrast, was more isotropically arranged. The results of the study have implications for the interpretation of biomechanical functionality of mouse AC with probable applications to other species.